I fantasmi e i corpi. Breve excursus sulla letteratura dei Latinos negli Stati Uniti (Altre Modernità, 2009)
The article shows the development of a distinctive Latino cultural tradition, linked to the immigration to the United States both from bordering Mexico (Mexican American immigrants, or chicanos) and from Puerto Rico (immigrants from la isla mainly to New York City, soon to be known as Nuyoricans). It retraces the complex and dramatic dynamics of both immigration trends, from the late 19th century to the late 20th century, and explores their cultural effects, both in terms of literary and theatrical production and in terms of socio-cultural behaviours more in general (class- and gender-based); and, by synthetically presenting some of these too often neglected authors and their works, it shows the important, critical and dialectical contribution offered by them to the literature(s) of the United States.